2013
DOI: 10.1111/imj.12157
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between glycaemia and length of hospital stay during an acute exacerbation of chronic obstructive pulmonary disease

Abstract: We have assessed whether glucose concentration and patient outcome are related in hospitalised patients when glycaemia is quantified in detail. Continuous glucose monitoring was performed on 47 consecutive subjects with an acute exacerbation of chronic obstructive pulmonary disease. Length of hospital stay increased by 10% for each mmol/L increase in mean glucose (P = 0.01). In a multivariable analysis, mean glucose was independently associated with length of hospital stay (P = 0.02). These data add weight to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
2
19
1
Order By: Relevance
“…Previous studies have shown that hyperglycemia during hospitalization is associated with poor outcomes in patients with COPD, which prolongs the length of stay and increases the risk of death in patients with acute exacerbated COPD19202122. However, in the present study, hyperglycemia did not have any significant predictive value for mortality in the fully adjusted survival analysis (P = 0.519).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Previous studies have shown that hyperglycemia during hospitalization is associated with poor outcomes in patients with COPD, which prolongs the length of stay and increases the risk of death in patients with acute exacerbated COPD19202122. However, in the present study, hyperglycemia did not have any significant predictive value for mortality in the fully adjusted survival analysis (P = 0.519).…”
Section: Discussioncontrasting
confidence: 87%
“…Hemoglobin level and oxygen and carbon dioxide partial pressures (PO 2 and PCO 2 , respectively) were also assessed. Finally, blood glucose level was also collected because recent research has found this variable to be correlated with COPD mortality19202122. The detailed study procedure is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…8 16 17 However, point-of-care glucometers are subject to greater analytical error than laboratory analysis of venous blood, which may reduce measurement precision. This is mitigated by the fact that, being less burdensome and costly, capillary glucose can be measured more frequently and thus better capture biological fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of this is probably multifactorial, including effects from systemic corticosteroid and inhaled β-agonist therapy,10 11 hypoxia,12 acidosis,13 and stress-related increases in glucose-elevating hormones 1415 Elevated blood glucose concentration is associated with prolonged hospital stay and death, the risk of which increases by 7%–15% for each 1 mmol/L increment in blood glucose concentration,7 16 17 and with failure of non-invasive ventilation 18. Whether these associations are causal is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…longer hospital stay and death) increasing by 15% for each 1-m M increment in blood glucose [11]. Moreover, it was also reported that the length of hospital stay after AECOPD increased by 10% for each 1-m M increase in mean glucose [40]. These findings suggest a potentially negative impact of the diabetic condition on AECOPD.…”
Section: The Impact Of Diabetes On Patients With Copdmentioning
confidence: 96%